The Quality of Kampar River Water inArea Lubuk Siam Village, Siak Hulu District Kampar, Province in Riau, Based on National Sanitation Foundation-Water Quality Index (NSF-WQI) - Heri Apriadi Siregar; Eni Sumiarsih; Muhammad Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract The Kampar River is one of the rivers in the province of Riau, which is in Bukit Barisan around the Province of West Sumatera and it rises on the east coast of Sumatera island. The National Sanitation Foundation-Water Quality Index (NSF-WQI) is an index method of water quality assessment to analyse both and poor water quality for the survival of aquatic organisms and water pollution control program assessment data. The purpose of this research is to determine the quality value of Kampar river water in Lubuk Siam Village area based on NSF-WQI. Measurement and sampling of the Kampar river water quality is conducted in February - March 2020. The measurement and sampling of water quality parameters is done at 3 research stations with 1 sampling point on the surface of the water. Measurement and sampling of water quality parameters at all three research stations is conducted 3 times with a time interval of one week. Some parameters of water quality to determine the index of NSF-WQI values are temperature, turbidity, total solids, pH, BOD, dissolved oxygen, nitrates, and total phosphate. The results of measuring water quality parameters at each station are as follows: Temperature 28,33–29,66 °c, turbidity 32,73–33,47 NTU, TSS 41,66–46,66 mg/L, dissolved oxygen 6.11–6.77 mg/L,pH 5, BOD5 3.85–4.59 mg/L, nitrate 0,0541–0,0715 mg/L, total P 0,1821–0,2345 mg/L. Quality assessment of Kampar River water in Lubuk Siam Village area based on NSF-WQI is 64,19–66,83 with moderate water quality criteria. The value of NSF-WQI on the Kampar River in Lubuk Siam Village area can still support the life of aquatic organisms.Keywords:Aquatic, Anayse,Kampar River, Method, Parameter, Value